Música e tradição: trajetória da Folia de Reis na Comunidade Quilombola do Mimoso - Araújo, Dinomar Rosa (Universidade Federal do Tocantins, 2020)
This study presented as its central theme the analysis of the Folia de Reis of the community of Mimoso, in the city of Arraias (TO), the intention was to develop a project linked to the knowledge and doings of this Quilombola Kalunga community, as well as to develop a physical record of the tradition of that community. The place can be considered difficult to access due to the poor conditions of the roads, and until recently, had no electricity supply. Its inhabitants are descendants of enslaved people who worked especially in the extraction of gold and have long been fighting for their rights, particularly for the right to the territory. Reisado is a party known and practiced since the time of colonization, in various regions of Brazil. Manifestation of popular catholicism that contemplates the celebrations in praise of the Magi reminding the history of the nativity. They prove to be an important way of representing and safeguarding popular culture. The present work approaches the ethnographic studies, which presuppose that the researcher acts in order to examine behavioral patterns and ways of life of a certain group. The work is based on theorists such as: Dantas (2018), Lourenço (2014), Bresler (2006), among others and is divided into three chapters, besides the final considerations. In the first chapter, a small bibliographic survey was made, discussing part of what was written about the subject; The theoretical framework was also presented. In the second chapter, it was the methodology and the process of data collection; In the third chapter, data analysis and some conclusions were presented. The work was carried out between November 2018 and October 2019, and data collection (field work) was carried out between December 2018 and January 2019. The research is qualitative and data were collected. through semi-structured interview, questionnaire, observations, videos and photos. The objectives were to record, study and describe the musical and cultural practices of Folia de Reis in the Mimoso region; know the history of the party and identify the people who keep the tradition alive, understanding the relevance of this festivity to the local culture. As a result, it became clear that there is a very strong relationship between music, image, faith and gestures. Being the flag the biggest symbol of faith of the party. It is revered and revered by all participants in the revelry in a relationship of devotion that has a strong connection with the sacred.